2020
DOI: 10.5371/hp.2020.32.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Bilateral Hip Fractures in Elderly Patients

Abstract: Sequential bilateral hip fractures (SBHF) have been reported with increasing frequency in elderly and osteoporotic patients 1) . Patients with SBHF have greater mortality, reduced functional abilities, limited mobility and seldom recover to their preoperative mobility levels [2][3][4] , therefore, it is crucial to fully understand SBHF, so that preventive and treatment strategies can be developed and initiated after an initial hip fracture, especially in elderly patients.Numerous studies have described the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our investigation revealed a second fracture rate of 8.7% following hip fracture surgery, which aligns with rates reported in Korea [14] is notably lower than those observed in Finland and Spain [15,16]. These variations in the rate of second fractures can be attributed to differences in inclusion and exclusion criteria across studies.…”
Section: Discussionsupporting
confidence: 86%
“…Our investigation revealed a second fracture rate of 8.7% following hip fracture surgery, which aligns with rates reported in Korea [14] is notably lower than those observed in Finland and Spain [15,16]. These variations in the rate of second fractures can be attributed to differences in inclusion and exclusion criteria across studies.…”
Section: Discussionsupporting
confidence: 86%
“…The time interval between the two hip fractures is crucial. The average reported time in literature fluctuates between 31 months and 168 months, with 2-39% occurring during the first postoperative year [ 2 , 8 - 12 , 23 ]. In accordance with the presented data, the mean time interval between the first and second hip fracture of our group of patients was 39.63±49.31 months; however, 29.62% of the patients sustained the second fracture in the first year, and 25.9% of the elderly had their second fracture during the second postoperative year.…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al. [ 23 ], in their analysis, noticed that the second hip fracture in the trochanteric region occurs earlier than in the neck region (29.1 months vs. 37.4 months). Because of our small sample size, we could not investigate this relationship in our population.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] These studies have demonstrated that being >60 years of age is a significant factor independently associated with higher mortality rates and increased postoperative complications. [14,15] In our study, we defined geriatric patients as those aged ≥60 years, utilizing the same criteria for classification.…”
Section: Study Description and Definitionsmentioning
confidence: 99%